The void of English - Terry Caesar (Revista Espaço Acadêmico, 2019)
I can’t write Portuguese. So my words must be translated in order to reach a Brazilian audience. However, I can teach English. My words must not be translated in order to reach a Japanese audience – otherwise it wouldn’t be teaching, or at least teaching English.